Introducing a Coopetition Model for Domestic Airlines in Iran - Saedeh Ghayourisales; Mohsen Nazari; Mohammadali Shahhoseini (‫مدیریت بازرگانی)
Objective This research aims to propose a coopetition model specifically designed for Iranian airline companies. As a result of shifts in both internal and external landscapes, along with the swift advancements in technology encapsulated by the term VUCA (signifying volatility, uncertainty, complexity, and ambiguity), the conventional dichotomy of pure competition or complete cooperation has diminished in its efficacy. In its place, a novel mode of collaboration has emerged, characterized by a blend of cooperation to generate value and competition in the pursuit of value, termed "co-competitiveness." Considerable research efforts have been dedicated to this strategy, and it has garnered significant attention on both a global and Iranian scale. Recognizing the significance of this subject from both theoretical and practical perspectives, and acknowledging the existing gap in the examination of competition within domestic airline companies, this article aims to investigate the factors, mechanisms, and outcomes of coopetition in this particular industry.